Comparison of some quality parameters in sour cherry juice in different packaging - Durmishi N., Xhabiri G., Alija E., Alija D., Karakasova Lj., Babanovska-Milenkovska F., Stamatovska V., Lazova-Borisova I. (International Journal of Food Technology and Nutrition, 2024)
Fruits and their products are of great importance in the food industry. Fruit juices are found in almost every market, which helps consumers to get nutritional value from their consumption. The quality and insurance must be at the right level, but even more important to apply permanent control. Sampling was carried out randomly directly in the supermarket, and the analysis of parameters in the study of sensory quality (color, taste, aroma, and homogeneity) and physical-chemical (pH, °Brix, total acidity, and turbidity) in sour cherry juice is of importance because the same juice in different packaging is compared. After the analyses that have been carried out and the results obtained, they provide additional insight into the analyzed parameters. So, the consumer receives additional information, also confidence in the quality of the product will increase based on the results obtained. In conclusion, even though we are talking about the same sour cherry juice, as a result of the % content of the raw material with different amounts and the different packaging, the analyses for the parameters under study prove the differences, but at the limit, so the analyzed juices are within the standard for quality.
Keywords: sour cherry juice, °Brix, total acidity, pH, turbidity, color, taste, aroma.